FIGURE 2 in A new species of Menestho Møller, 1842 from the Arctic with remarks on Menestho albula (Fabricius, 1780) (Gastropoda: Heterobranchia: Pyramidellidae) - Nekhaev, Ivan O. (Zenodo, 2017)
FIGURE 2. Teleoconchs (A-D), operculum (E), embryonic shells (F-H) and details of sculpture (I-K) of the Arctic species of Menestho, SEM micrographs. A, E, G, I—Menestho schikovi sp.n.: A, I—holotype, E, G—Kara Sea, 76°41'N, 88°14'E, 45 m (G - same specimen as on Fig. 1C); B, F—Menestho truncatula, Kara Sea, 79°17.2'N, 76°03'E, 54 m; C-D, H, J-K—Menestho albula, C, J—Barents Sea, Murman Coast, Dalne-Zelenetskaya Bay, 69°07.85'N, 36°04.81'E, 46 m (same specimen as on Fig. 1B), H—Barents Sea, Murman Coast, Kola Inlet, 69°18.90'N, 33°29.08'E, 43 m, D, K—between Labrador and Greenland; Scale bars: A-D at same scale bar = 3 mm, E = 500 µm, F-H at same scale bar = 200 µm, scale bars for I, J, K = 200 µm. Arrows indicate direction of growthlines. Published as part of Nekhaev, Ivan O., 2017, Zootaxa 4347 (1) , DOI:10.11646/zootaxa.4347.1.13, http://zenodo.org/record/1044820